Insite or Outside the Law: Examining the Place of Safe Injection Sites within the Canadian Legal System - Aidan Macdonald (Oñati Socio-Legal Series)
In response to the mounting number of HIV/AIDS and overdose deaths directly attributable to intravenous drug use during the 1980 and 1990’s, governments across the world began considering alternatives to traditional prohibitionist drug policies. These alternatives, generally described as harm reduction strategies involving needle exchange programs and safe injection sites, rapidly gained acceptance across Europe. By contrast, they encountered significant opposition in North America. This thesis summarily traces the history of Canadian drug law, describing the development and impact of the harm reduction movement in Canada and the establishment of the first and only safe injection site (SIS) in North America (Insite). Employing a repressive formalist analysis of the application of federal drug laws, I then examine the role of the current Conservative government in contesting harm reduction strategies and refusing full legalization of Insite. I illustrate that through the strategic manipulation and discriminatory enforcement of drug laws and political gamesmanship relating to the criteria grounding Insite’s exemption from current drug laws, the government has failed to fulfill a set of fundamental social values with respect to Insite’s users and members of the downtown eastside of Vancouver. Interviews with injection drug users, workers at Insite and residents of the local community provide empirical support for the beneficial effects of safe injection sites, and expose the politics of the struggle for Insite’s continued existence. I also show how the Conservative anti-drug ideologues have led a resistance against classifying drug addiction as a health-related rather than criminal problem, despite significant scientific evidence to the contrary, and how this resistance has resulted in the further marginalization of injection drug users.